Influence of temperature and concentration of soluble solids on the rheological behavior of cocona pulp - Leandro Laguna, Caleb (2022)
Cocona is a delicious fruit that grows in the Peruvian Amazon, located east of the Andes. The study of the physical properties of the pulp, including its rheology, is necessary to optimize the different stages and processes for its industrialization. The objective of this work was to evaluate the influence of temperature (Tp) and the concentration of soluble solids (Cp) on the rheological behavior of cocona pulp. The variables of Tp (30 – 60 °C) and Cp (10 – 25 °Brix) were varied according to a 4 × 4 factorial design with three repetitions. Ripe fruits showed biometric characteristics of weight (210.2 g), axial diameter (85.47 mm), and equatorial diameter (65.56 mm) before being pulped. The physicochemical characteristics of the pulp were: soluble solids (6.51 °Brix), pH (3.62), acidity (1.42 g of citric acid/100 g of pulp), and moisture (86.57%). The concentration of the pulp was carried out with the addition of commercial white sugar, as a preservative agent. Rheological measurements were evaluated in a Brookfield rotational viscometer. The rheological parameters helped to calculate the consistency index (K: 48,63 a 111,14 Pa·sn) and flow index (n: 0,271 a 0,353) through the Power Law mathematical model for predictive purposes (R2 > 0.9), under the studied domain. The evaluated pulps revealed a non-Newtonian behavior of the pseudoplastic type and the activation energy varied from 11.55 to 14.81 kJ/mol. These results can be used for future work, quality parameters, and equipment design.